Tc1/Tc2 and Th1/Th2 balance in Asian and Western types of multiple sclerosis, HTLV-I-associated myelopathy/tropical spastic paraparesis and hyperIgEaemic myelitis - Ochi, Hirofumi; Wu, Xiao-Mu; Osoegawa, Manabu; Horiuchi, Izumi; Minohara, Motozumi; Murai, Hiroyuki; Ohyagi, Yasumasa; Furuya, Hirokazu; Kira, Jun-ichi (Journal of neuroimmunology, 2001)
CD8 + T cells, like CD4 + T cells, can differentiate into at least two subsets with distinct cytokine patterns: Tc1 cells produce Th1-like cytokines and Tc2 cells produce Th2-like cytokines. To clarify the immunopathological roles of Tc1 and Tc2 cells in central nervous system (CNS) inflammation, we examined intracellular cytokines in CD8 + and CD4 + T cells by flow cytometry and analyzed the Tc1/Tc2 balance as well as the Th1/Th2 balance in 80 patients with various CNS inflammatory diseases, including 20 with optico-spinal multiple sclerosis (OS-MS), 21 with conventional MS (C-MS), 22 with human T-lymphotropic virus type I (HTLV-I)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and 17 with hyperIgEaemic myelitis. Twenty-two healthy subjects were also examined as controls. Patients with OS-MS showed a significantly higher percentage of INF-γ +IL-4 − CD8 + T cells as well as CD4 + T cells and a significantly higher intracellular interferon-γ (IFN-γ)/interleukin-4 (IL-4) ratio both in CD8 + and CD4 + T cells throughout the relapse and remission phases than the healthy controls. Furthermore, the patients with OS-MS showed a significantly lower percentage of INF-γ -IL-4 + CD4 + T cells as well as CD8 + T cells during the relapse phase than the healthy controls. On the other hand, the patients with C-MS showed a significantly higher percentage of IFN-γ −IL-4 + CD8 + T cells in addition to more IFN-γ +IL-4 − CD4 + T cells during the relapse phase than the healthy controls. The HAM/TSP patients showed a significantly higher percentage of INF-γ +IL-4 − CD8 + T cells and a significantly higher intracellular IFN-γ/IL-4 ratio in CD8 + T cells than the healthy controls. In contrast, in hyperIgEaemic myelitis, in addition to a significantly lower intracellular IFN-γ/IL-4 ratio in CD4 + T cells, a tendency toward a lower intracellular IFN-γ/IL-4 ratio in CD8 + T cells in comparison to the healthy controls was observed. These results clarified for the first time the distinct Tc1/Tc2 balance in each disease condition as follows: Tc1 cell response is predominant in OS-MS and HAM/TSP, while Tc2 cell response is predominant in hyperIgEaemic myelitis and at relapse phase of C-MS. Furthermore, our results suggest that CD8 + T cells play an adjunctive role in disease induction and the clinical course of MS.